Analyzing the Efficient Allocation of Sago Processing Business Production Factors in East Kolaka District - Nursalam Nursalam (School of Business, IPB University (SB-IPB), 2018)
Sago has been widely cultivated or nourished for a long time by farmers and traditional communities in some areas such as East Kolaka District of Southeast Sulawesi Province. The purpose of this research was to know the allocation of production factors in producing sago flour and to analyze the efficiency and condition of Return to Scale of sago processing business in East Kolaka District. This research used a descriptive analysis method. The data used were primary data and secondary data. The data obtained were tested by multiple linear regression and RTS test. Based on the results of the research, it was concluded that the average revenue of semi-mechanical sago processing business per month was Rp 6,881,524. Based on the analysis result, it was known that NPMx/Px of the number of sago stem was 8.78; the number of labour was 1.93, and fuel usage was 3.07 where the numbers were greater than 1. It means that the number of processed sago stems had not been economically efficient. From the efficiency of production factor, it can be concluded that the number of processed sago stems, the number of labour, and the fuel usage was not efficient yet.Keywords: sago processing, analysis of efficiency, revenue, production factor, return to scale